Hubungan Dukungan Ayah ASI Terhadap Pemberian ASI Eksklusif - Fatimah; Roza Adila, Dian; Niriyah, Sekani (Jurnal Ilmu Keperawatan, 2023)
Father's support for breastfeeding is one of the factors that influence a mother to breastfeed exclusively. This study aims to find out the relationship between father's support and exclusive breastfeeding. This type of research is quantitative using a descriptive correlational design and a cross-sectional approach. The sample for this study consists of 50 respondents who are mothers with babies aged 0-6 months who are registered at the Langsat Health Center. Sampling uses random sampling techniques. Data collection using questionnaires. Analysis in this study uses bivariate with the Chi-Square test. The result of the study on the characteristics of respondents aged 26-35 years is a total of 29 respondents (58%), the average number of respondents who are multiparous is 33 respondents (66%), the average ethnicity of the mother is Malay is 26 people. respondents (52%), the average mother's education, i.e. secondary education, was obtained by 34 respondents (68%), the average mother's occupation, i.e. not working, was obtained by 35 respondents (70%), while the father's education, i.e. secondary education, was obtained by 35 respondents (70%) and the average occupation of the father is self-employment. There are 21 respondents (42%). The results of the study showed that exclusive breastfeeding was obtained by 37 respondents (74%), and good breastfeeding father support was obtained by 25 respondents (50%). Bivariate analysis using the Chi-Square test showed a P value of 0.107 (P>0.05), meaning that there is no relationship between breastfeeding father support and exclusive breastfeeding. The community health center is expected to educate the community about the importance of the family's role in the influence of exclusive breastfeeding. Keyword : Exclusive Breastfeeding, Breastfeeding Father